2021
DOI: 10.1038/s41586-020-03116-4
|View full text |Cite
|
Sign up to set email alerts
|

Gut-licensed IFNγ+ NK cells drive LAMP1+TRAIL+ anti-inflammatory astrocytes

Abstract: Astrocytes are glial cells that are abundant in the central nervous system (CNS) and that have important homeostatic and disease-promoting functions1. However, little is known about the homeostatic anti-inflammatory activities of astrocytes and their regulation. Here, using high-throughput flow cytometry screening, single-cell RNA sequencing and CRISPR-Cas9-based cell-specific in vivo genetic perturbations in mice, we identify a subset of astrocytes that expresses the lysosomal protein LAMP12 and the death rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
177
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(182 citation statements)
references
References 92 publications
(140 reference statements)
3
177
0
2
Order By: Relevance
“…Using these complementary models, we demonstrated a protective effect of NK cells on recovery of motor behavior in vivo . It was shown that NK cells induce homeostatic anti-inflammatory activities of astrocytes via IFN-γ (Hindinger et al, 2012; Sanmarco et al, 2021). Indeed, astrocytes were found to be activated in ischemic stroke already at P3 (Werner et al, 2020), at the same time when the effect of NK cell absence was observed in our beam-walk sensorimotor test.…”
Section: Discussionmentioning
confidence: 99%
“…Using these complementary models, we demonstrated a protective effect of NK cells on recovery of motor behavior in vivo . It was shown that NK cells induce homeostatic anti-inflammatory activities of astrocytes via IFN-γ (Hindinger et al, 2012; Sanmarco et al, 2021). Indeed, astrocytes were found to be activated in ischemic stroke already at P3 (Werner et al, 2020), at the same time when the effect of NK cell absence was observed in our beam-walk sensorimotor test.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, it was demonstrated by a high-speed flow cytometry screening experiment, single-cell RNA sequencing, and CRISPR–Cas9-based cell-specific in vivo genetic disturbances in mice that there is a set of astrocytes in the central nervous system that can limit inflammation by inducing T-cell apoptosis, receiving signals from the gut bacteria that stimulate anti-inflammatory activity under the action of interferon-γ (IFNγ) produced by natural killer meningeal cells, in which IFNγ expression is modulated by the intestinal microbiome [ 272 ].…”
Section: Photobiomodulation Applied On the Gut–lung–brain Axismentioning
confidence: 99%
“…For example, Wheeler et al [ 37 ] showed that reduced astrocyte expression of the Nuclear factor erythroid 2-related factor 2 (NRF2) was correlated with increased production of the small musculoaponeurotic fibrosarcoma G (MAFG) proteins that enhance the inflammatory responses of infiltrating T-cells in EAE mouse models. The same research group showed that astrocytes expressing high levels of lysosome-associated membrane protein 1 (LAMP-1) and the TNF-related apoptosis-inducing ligand (TRAIL) promoted apoptosis of infiltrating T-cells, thus performing an anti-inflammatory activity [ 131 ]. On the other hand, astrocyte expression of these markers was found to depend on their interactions with infiltrating NK cells, secreting the cytokine IFN-γ, and was inhibited by other cytokines such as tumor necrosis factor (TNF) and interleukin 1α (IL-1α), secreted by T cells.…”
Section: Astrocytesmentioning
confidence: 99%